A High-Fat Diet Aggravates the Age-Related Decline in Skeletal Muscle Structure and Function. Issue 4 (October 2021) - Degens, Hans; Swaminathan, Anandini; Tallis, Jason
Abstract : The age-related decline in muscle function is aggravated by a high-fat diet (HFD)-induced increase in fat mass. The hypothesis is that an HFD leads to a faster accumulation of intramyocellular lipids (IMCL) and an earlier onset of muscle dysfunction in old than in young-adult individuals. The IMCL accumulation is attenuated in young-adult organisms by an elevated oxidative capacity. Methionine restriction enhances mitochondrial biogenesis and is promising to combat obesity across the ages. Abstract : The negative effects of a high-fat diet on skeletal muscle structure and function occur earlier in old age.